A to Z of the Designers Republic / Ian Anderson. - Anderson, Ian (Thames & Hudson Ltd, 2023)
Led by founder and born rebel, Ian Anderson, the Designers Republic has shaped graphic communication over the past 30 years through rule-defying music work, provocative self-initiated projects and a fierce commitment to conceptual thinking over style. Now, for the first time in book form, Anderson explores the studio's output, and its influence on a generation of graphic designers.